Two new Gorgonopsian skulls - Manten, A. A. (Bernard Price Institute for Palaeontological Research, 1959)
Two complete and well-preserved skulls are described. One is referred to the species Gorgonops torvus Owen. It gives information on several details that are not clear in the type specimen. The second skull is recognized as a new species of Prorubidgea, and named Prorubidgea brinki.
Main article
Keywords: Gorgonopsian; skull